Transdutor a fibra ótica para análise de biodiesel e misturas BX - Heidemann, Bárbara Rutyna (2011)
An alternative for the traditional biodiesel and BX blends analysis (X is the biodiesel volumetric concentration in the blend), such as chromatography, spectroscopy and nuclear magnetic resonance, is by means of an optical fiber refractive index transducer, such as an LPG. However, as the biodiesel and diesel refractive index are close or bigger than the fiber cladding index, there is an important loss of power to the surrounding environment, impairing the sensor performance. In order to decrease the refractive index of biodiesel, a miscible and low refractive index substance, cyclohexane, was chosen to blend to this biofuel and also to the biodiesel-diesel blend. The results show that the cyclohexane does not react with biodiesel, acting only as a solvent. Besides, the 1:1 and 1:2 dilution (one part of BX blend and one part of cyclohexane in volume concentration; one part of BX blend and two parts of cyclohexane in volume concentration) have a refractive index lower than the fiber cladding, what shifts the resonant band of the LPG towards lower wavelengths. After representing the calibration curves in graphics of wavelength shift (nm) as function of biodiesel-diesel blend concentration, BX (% v/v), for both dilution, the concentration sensitivity has been obtained. The metrological characteristics were calculated, leading to the expanded uncertainty, which is 3,7 % for the 1:1 dilution and 5,9 % for the 1:2 dilution, for a 95,45 % confidence level.